O valor da dádiva e o sentido da vida na experiência de membros do Narcóticos Anônimos: um estudo compreensivo. - Barros, Mateus Souto Maior (2020)
Recent research such as the global report on drugs, carried out by the United Nations Organization, and statistical surveys on drug use, carried out by the Brazilian Center for Information about Psychotropic Drugs, point to a reality of both the growth of drug use in Brazil, and the world, how much of an insufficient supply of treatments for people with disorders associated with this use. Among the universe of treatments offered for this problem is a Narcotics Anonymous (NA) entity comprised of Addicts - their names for problematic drug users - who help each other recover from the disease of addiction - characterized by problematic drug use and behavioral changes associated with use. The entity's treatment program is composed of two main tools: the Mutual Help Groups and the Twelve Steps program. Mutual aid groups occur freely and voluntarily, and are attended only by addict members and their family members-in case the meeting is open. Looking at the way they organize and work in the program, here is the guiding question for the survey: "How did the life experience of the members of Narcotics Anonymous come to be about rebuilding their lives? And what does this have to do with helping each other? The mutual help present in the work of the entity was understood from the Gift, a sociological paradigm, elaborated by Marcel Mauss, about the formation of social bonds based on the symbolism of exchange, volunteering, and solidarity, present in a cycle that involves obligations to give, receive, give back, and transcend. The individual efforts to change life were reflected on the basis of Viktor Frankl's Logotherapy and Existential Analysis, which understands man in the search for a Meaning of Life. The general objective of the study was to understand the value of Gift and Meaning of Life in the experience of members of Narcotics Anonymous. The specific objectives were: 1. Study the history, method of working, and organization of Narcotics Anonymous; 2. Analyze the relationship between the theory of giving and NA's self- help groups; 3. Investigate the relationships between some of Viktor Frankl's Logotherapy and Existential Analysis concepts and NA members' efforts to change. The methodological path followed in the research included the tools Field Diary and Narrative Interview based on Walter Benjamin. The interviews were conducted with five members, four men and one woman, and there was a triggering question: "Please comment on your experience becoming a member of Narcotics Anonymous. From the narrative answer to the triggering question, other questions were inserted to fully contemplate the object of the research. The data were analyzed from Gadamer's Philosophical Hermeneutics. In the final preparation of the results, the notes of the Field Diary and the theoretical reflection in the light of Viktor Frankl's Logotherapy and Existential Analysis and Marcel Mauss' Gift were also considered. At the end, it was concluded that the objectives were achieved, since Gift and Meaning of Life allowed a broad understanding of the experiences of members of the NA entity. It was also reflected on how much the experiences varied according to the time of attendance, age, social conditions, race, and gender of the members. These variations signaled the need for future research on the work of the entity in each of its aspects.